Early cellular immune response to Leishmania major and modifying effect of sand fly salivary gland proteins - Rogers, Kathleen A., author; Titus, Richard G., advisor; Avery, Anne, committee member; Cooper, Andrea, committee member; Callahan, Gerald, committee member (Colorado State University. Libraries, 2001)
The protozoan parasite Leishmania major is transmitted by the bite of an infected phlebotomine sand fly. The resulting disease, leishmaniasis, manifests itself as ulcerated skin lesions that can take months to resolve. This model has been used to characterize the T helper type-1 (Th1)/ T helper type-2 (Th2) paradigm for cellular immune responses. Th1/Th2 responses are distinguished by the cytokines secreted and selective activation of the cells, resulting in the development of a cellular or humoral immune response respectively. In leishmaniasis, a Th1 response, primarily characterized by the production of IFN-γ, will result in an inflammatory response capable of controlling most intracellular infections. On the other hand, a Th2 response, characterized by the production of IL-4. IL-5 and IL-10. drives primarily a humoral response, the hallmark being the production of high titers of antibodies. In L major infections, a Th2 response results in disease exacerbation. Most experiments studying the human immune response to the parasite involve subjects already infected with the disease. As cytokine production can begin within hours to days of a Leishmania infection and could in turn establish the cytokine microenvironment leading to a Th1 or Th2 response, we wanted to examine the human response during the acute infection phase. Peripheral blood mononuclear cells (PBMC) from Leishmania-naive donors were isolated and exposed to L. major. The interactions of the cells and the parasite were evaluated during the first week of infection, during primary exposure, as well as upon restimulation with L. major after a week of primary stimulation. This system was characterized by phenotypic analysis (e.g. CD4 expression) as well as by cytokine secretion (e.g. IFN-γ). We found that both CD4+ and CD8+ T cells responded to L. major and that Type 1 cytokines were primarily produced. The influence of exogenous cytokines or neutralizing antibodies on the production of Th1 and Th2 cytokines at 3 and 7 days was also examined. We found that that the cytokine most influenced by either Th1-like cytokines (e.g., EL-12) or Th2-like cytokines (e.g., TGF-β) was IFN-γ, suggesting that in humans, this cytokine has dominant role in immune modulation during the infection. When sand flies inject L major into the vertebrate host, they also inject immunomodulatory salivary proteins. Using the in vitro system developed, the modifying effects of sand fly salivary gland lysate, as well as Maxadilan. a potent vasodilatory peptide isolated from sand fly saliva, were determined on PBMC and monocyte/macrophage cultures. Both Maxadilan and saliva decreased IFN-γ production of PBMC and increased IL-6 production in monocyte/macrophages. Maxadilan appears to interact with macrophages through the neuropeptide receptor, pituitary adenylate cyclase activating peptide (PACAP).
Keywords: immunology; microbiology